1998
DOI: 10.1103/physrevb.57.r6838
|View full text |Cite
|
Sign up to set email alerts
|

Relocation time of the domain boundary in weakly coupled GaAs/AlAs superlattices

Abstract: Static domain formation in doped semiconductor superlattices results in many branches in the currentvoltage characteristic separated by a discontinuity in the current. The transition process from one branch to the next has been studied experimentally by adding an ac bias with different amplitudes to a dc bias close to a discontinuity and recording the time-resolved current. The relocation time of the domain boundary depends exponentially on the difference between the final static current and the maximum or min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
46
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 8 publications
4
46
0
Order By: Relevance
“…These figures are qualitatively similar to the corresponding ones depicted from experimental data in Refs. [9] and [5]. Quantitative differences are due to the above mentioned discrepancies in F M , the tunneling current and the shot noise amplitude.…”
Section: Numerical Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…These figures are qualitatively similar to the corresponding ones depicted from experimental data in Refs. [9] and [5]. Quantitative differences are due to the above mentioned discrepancies in F M , the tunneling current and the shot noise amplitude.…”
Section: Numerical Resultsmentioning
confidence: 97%
“…In Ref. [5] it was claimed that the time delay depends exponentially on the difference between the final value of the stabilized current, I, and the maximum value of the current (or mimimum value in the case of a down switch) at the initial branch, I m . Then the relocation time (measured in units of 1.021 ns) depends exponentially on the current difference I − I m , i.e.,…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7]. Recent experiments [8,9] with such devices have demonstrated that near the boundary of the bistable region one of the two states is metastable, and its lifetime has been studied by measuring current as a function of time at different voltages. Thus, these devices provide an ideal experimental system for studying the decay of metastable states in real time.…”
mentioning
confidence: 99%